Pengaruh Financial technology, Literasi Keuangan dan Financial Self Efficacy terhadap Pengelolaan Keuangan UMK Kuliner di Kota Jambi - Lestari, Lintang; Setiawati, Rike; Utama, Ahmad Nur Budi (Universitas Batanghari Jambi, 2024)
A In this case, the sustainability of the UMK must be observed and can beined by doing good financial management. This is because the financial management can help the stakeholders in controlling the output and input, help improve efficiency and efficiency as well as be able to minimize financial risk. This research aims to find out the impact of the use of financial technology based on digital payment in particular e-wallet, financial literacy and financial self efficacy of the culinary UMK actors in Jambi City. The study used a quantitative approach with a sample of 377 respondents. The data used are primary and secondary data using questionnaires and references from some related literature. The data analysis method in this study uses SmartPLS 4. The results of this study show a positive and significant influence of the variables used Financial technology, financial literacy and financial self efficacy on financial management.